DESIGN OF HOUSEHOLD HAZARDOUS WASTE LANDFILL IN LEUWIGAJAH EX-LANDFILL - Iyanuar, Monica
The final processing place (TPA) is a place to process and return waste to the environment media, usually in the form of landfill. At present, in Indonesia, mostly in large cities, domestic (household) landfill that is used can be categorized as hazardous landfill because during landfilling, nonhazardous household wastes are still mixed with household hazardous waste. Household hazardous waste is residue of household activities that contain corrosive, toxic, flammable and reactive material such as paints, batteries, lights, and so on. According to Law of Republic Indonesia No. 18 of 2008, household hazardous waste is categorized as specific waste containing hazardous material which requires special management. Based on the results of data collection, the average number of hazardous waste generation amounts is about 2% of the total domestic waste generation (0.4097 kg/person /day), with 55% toxic waste, 8% corrosive waste, 24% reactive waste, and 13% flammable waste. The collection of household hazardous waste data is carried out using the method approach of SNI 19-3964-1994 regarding the Method of Taking and Measuring Examples of Occurrence and Composition of Urban Waste because there are no specific regulations governing household hazardous waste. Although the number of household hazardous waste generation is small, but accumulation of hazardous material on landfills can endanger the environment and the community around the landfill area. Therefore, a special landfill for household hazardous waste is needed. Recommendations for facilities built in the final processing place of household hazardous waste include basic facilities, supporting facilities, operational facilities, collection facilities, procurement and processing of leachate facilities, sorting facilities, crushing facilities, and processing facilities. The design of landfill capacity is 681,733.40 m3, with a service life of 12 years and 11 months. The landfill used consisted of a sanitary landfill with a class of landfill, class I, consisting of a base layer, the second geomembrane layer, a layer for leak detection systems, a barrier layer, the first geomembrane layer, layer for leachate transfer and collection system, and layer protectors during operation. Based on TCLP test results, the element Zinc (Zn) results exceed the quality standard, which is equal to 324.67 mg/L (sample 1) and 406.5 mg/L (sample 2). The content of Zn mostly comes from electronic waste. At the sorting facility segregation of waste batteries, lamps, electronic cables, other electronic waste and hazardous packaging which still contains hazardous liquid waste is then processed first before stockpiling.